2021
DOI: 10.1177/00131245211048426
|View full text |Cite
|
Sign up to set email alerts
|

How to Reform Without Reforming: School District Racial Composition and Pennsylvania’s “Fair” Funding Formula

Abstract: In the United States, researchers have documented persistent racial disparities in school funding for decades. Drawing on evidence from a recent policy change in Pennsylvania, this article contributes to research on the role of state governments in limiting or expanding racial disparities in K-12 education funding by examining differences in the racial composition of school districts positively and negatively impacted by a technical provision lawmakers inserted into a newly created formula for distributing sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This provision resulted in less than 10% of state equalization aid actually being distributed based on current student and district needs. The school districts that were negatively impacted by this provision were disproportionately Black and Latinx (Kelly, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This provision resulted in less than 10% of state equalization aid actually being distributed based on current student and district needs. The school districts that were negatively impacted by this provision were disproportionately Black and Latinx (Kelly, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In decline years, states may employ a hold-harmless provision under which state aid continues to be the same as that of the previous year despite the decline in enrollment. Scholars have argued that this hold-harmless provision competes with charter schools (Roza & Fullerton, 2013), violates the principle of horizontal equity (Fahy, 2011), and may produce racial disparities (Kelly, 2021). Gigliotti and Sorensen (2018) examined the effects of the hold-harmless provision in New York and found that this provision did not significantly affect instructional spending but did increase administrative spending.…”
Section: Introductionmentioning
confidence: 99%